THE IMAGE OF THE FATHER AND TRADITIONAL VALUES IN THE WORKS OF MARCEL PAGNOL - Rakhmankulova Dilafruz Azimovna (International Journal of Literature and Language Studies, 2026)
This article is devoted to the study of the works of Marcel Pagnol, one of the prominent representatives of twentieth-century French literature, with particular emphasis on his autobiographical tetralogy, including the novels My Father’s Glory and My Mother’s Castle. In these works, the author skillfully reveals the image of the father as a moral ideal and mentor, emphasizing the significance of family values in the formation of an individual’s personality. In the context of contemporary transformations in family institutions, the artistic representation of traditional values has become an especially relevant issue. The aim of the study is to analyze the image of the father and traditional values in Pagnol’s works. The research methodology includes biographical, cultural-historical, comparative-typological, and hermeneutic approaches, which allow for a deeper understanding of the role of family traditions in the process of growing up and shaping the inner world of the character. The article contributes to a more profound understanding of human relationships and the values that remain significant in a changing society.